Enhancing students’ understanding of listening strategies through ubiquitous learning (video-based learning) - Rochmawati (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
This article presents a thorough case study examining the efficacy of video-based learning in enhancing students’ comprehension of listening strategies. The study was conducted in a university and focused on a cohort of 57 students who faced listening skills problems such as quickly forgetting what was heard or unfamiliar with the words. These students were exposed to meticulously designed video lessons to refine their listening skills and apply strategic techniques. A robust data collection methodology was employed to assess the impact of video-based learning, including systematic classroom observations and detailed feedback gathered through student questionnaires and in-depth interviews. The analysis of the collected data revealed compelling results, indicating a significant improvement in the students’ understanding of listening strategies following their engagement with video-based learning. These findings underscore the effectiveness of video in enhancing students’ listening skills. The data was presented in statistics, which showed that 52.6 % of students agreed that learning through video helped their understanding of the materials. Furthermore, this research highlights the critical role of technology-enhanced pedagogical approaches in modern education, one of which is using ubiquitous learning, namely video-based learning. Also, the data showed that 59.6 % of students felt the positive benefits of video-based learning, which can be accessed anywhere and anytime. In the end, this research contributes valuable empirical evidence that supports the integration of video-based learning as a strategy tool for improving students’ understanding of listening material, thereby paving the way for more effective educational practices.